Finding your Bus: Conceptualising Contemporary Quaker Management Education. Issue 2 (December 2019) - Lingelbach, David
Abstract : How can Quaker thought and practice make a significant contribution to contemporary management education? Quaker-affiliated businesses and organisations have played significant roles in both the United Kingdom and the United States. Yet the distinctive business practices underlying these businesses and organisations have had little impact on management education. Moreover, Quaker educational practices—developed over more than 300 years—have not had a meaningful influence on management education. Management education critiques have argued for greater attention to universal values and self-conception, both of which support an enhanced role for Quaker management education. This paper seeks to conceptualise contemporary Quaker management education. It describes key tenets of Quaker management practices and education as they relate to management education. It conceptualises Quaker management education as the nexus between Quaker management and educational practices. Its curriculum should inculcate the distinctive practices that contributed to the past success of Quaker enterprises and educational institutions.